Identification and functional analysis of circular RNAs in intervertebral disc lesion tissues from spinal tuberculosis patients - Wang, Linan; Duan, Xingyu; Qu, Yuliang; Shi, Zhiyun; Zhang, Xu; Yang, Zongqiang; Gao, Yingchao; Niu, Ningkui (Frontiers in Physiology, 2025)
BackgroundSpinal tuberculosis (STB) is characterized by an insidious onset, nonspecific clinical manifestations, and diagnostic challenges in early stages. Circular RNAs (circRNAs), a class of stable single-stranded endogenous RNAs with covalently closed-loop structures, play crucial regulatory roles in various biological processes. However, their involvement in STB pathogenesis remains largely unexplored.MethodsWe collected intervertebral disc tissue specimens and peripheral blood samples from STB patients. CircRNAs sequencing was performed on three representative lesion tissues, followed by comprehensive screening and validation in both tissue and blood samples to elucidate the functional mechanisms of circRNAs in STB.ResultsChip sequencing indicated that a total of 1,396 circRNAs were differentially expressed (fold change >2, P < 0.05). Among them, 757 circRNAs were upregulated, while 639 were downregulated. GO analysis of the parental genes of these differentially expressed circRNAs demonstrated that they were predominantly involved in cellular protein catabolic processes, GTPase binding, covalent chromatin modification, histone modification, and other processes. KEGG pathway analysis revealed that these genes were mainly enriched in signal pathways such as protein processing in the endoplasmic reticulum, apoptosis, and proteolysis. Validation in peripheral blood samples showed that the expressions of hsa_circ_0001021, hsa_circ_0043898, and hsa_circ_0093669 were significantly higher in the preoperative group than in the control group (P < 0.05). Moreover, the expression levels of these circRNAs decreased at 6 months and 1 year postoperatively compared to the preoperative levels. ROC curve analysis suggested that these circRNAs could serve as promising diagnostic biomarkers for STB in academic research scenarios.ConclusionThe differentially expressed circRNAs identified in intervertebral disc lesions of STB patients demonstrate significant involvement in disease pathogenesis, positioning them as promising candidates for both diagnostic and therapeutic targeting. Specifically, hsa_circ_0001021, hsa_circ_0043898, and hsa_circ_0093669 exhibit robust potential as peripheral blood-based diagnostic biomarkers for STB. When combined with conventional inflammatory markers ESR and CRP, these circRNAs significantly enhance diagnostic accuracy. Furthermore, longitudinal monitoring revealed their unique value in postoperative therapeutic evaluation, with expression levels showing strong correlation with treatment response.